ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG NIRA DI KABUPATEN DELI SERDANG - Kartika Mutia Ritonga; Rahma Sari Siregar; Khairul Saleh (Universitas Medan Area, 2021)
This study aims to determine the factors that influence the income of nira traders in Deli Serdang Regency. This research uses descriptive research type with a quantitative approach. This research was conducted from July to September 2019 in Deli Serdang Regency with a sample of 30 nira traders taken through saturated sampling techniques or censuses. Meanwhile, the data collection method used questionnaires and interviews. The results showed that the average income obtained by nira traders in Deli Serdang Regency was IDR 1,162,167 per month. Has a positive and significant effect on the income of nira traders in Deli Serdang Regency. Meanwhile, the selling price variable has no effect on the income of the nira traders in Deli Serdang Regency.Furthermore, the variables of working capital, selling price, experience and business location simultaniosly have a significant effect on the income of the nira traders in Deli Serdang Regency. This effect is 92.8% and the remaining 7.2% is explained byother variables.